2016
DOI: 10.1074/jbc.m115.708255
|View full text |Cite
|
Sign up to set email alerts
|

Bithionol Potently Inhibits Human Soluble Adenylyl Cyclase through Binding to the Allosteric Activator Site

Abstract: The signaling molecule cAMP regulates functions ranging from bacterial transcription to mammalian memory. In mammals, cAMP is synthesized by nine transmembrane adenylyl cyclases (ACs) and one soluble AC (sAC). Despite similarities in their catalytic domains, these ACs differ in regulation. Transmembrane ACs respond to G proteins, whereas sAC is uniquely activated by bicarbonate. Via bicarbonate regulation, sAC acts as a physiological sensor for pH/bicarbonate/CO 2 , and it has been implicated as a therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Our study leveraged reported, available pharmacologic tools including K Na 1.1 activators (bithionol and loxapine) as well as blockers (quinidine and bepridil) to begin to address the mechanism of gain‐of‐function . Bithionol, an anti‐helminthic drug that additionally activates BK channels, is understood mechanistically to be an allosteric modulator of K Na 1.1 through inhibition of soluble adenylyl cyclase . While K Na 1.1 is thought to be ATP‐insensitive as it lacks the ATP binding domain of its family member KNa 2.1 (encoded by KCNT2) , it is sensitive to divalent cation concentration, which also changes with inhibition of adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study leveraged reported, available pharmacologic tools including K Na 1.1 activators (bithionol and loxapine) as well as blockers (quinidine and bepridil) to begin to address the mechanism of gain‐of‐function . Bithionol, an anti‐helminthic drug that additionally activates BK channels, is understood mechanistically to be an allosteric modulator of K Na 1.1 through inhibition of soluble adenylyl cyclase . While K Na 1.1 is thought to be ATP‐insensitive as it lacks the ATP binding domain of its family member KNa 2.1 (encoded by KCNT2) , it is sensitive to divalent cation concentration, which also changes with inhibition of adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…Bithionol, an anti‐helminthic drug that additionally activates BK channels, is understood mechanistically to be an allosteric modulator of K Na 1.1 through inhibition of soluble adenylyl cyclase . While K Na 1.1 is thought to be ATP‐insensitive as it lacks the ATP binding domain of its family member KNa 2.1 (encoded by KCNT2) , it is sensitive to divalent cation concentration, which also changes with inhibition of adenylyl cyclase. Importantly, our study demonstrated that the KCNT1 ‐L437F pathogenic variant is not activated by either compound with presumably different mechanisms of action, whereas current conducted by the wild‐type channel is dramatically increased, suggesting the L437F channel is already maximally conducting, with a high open probability.…”
Section: Discussionmentioning
confidence: 99%
“…However, both KH7 and ASI-8 are long compounds which would extend into the active site and inhibit, at least partially, via competition with the substrate. In fact, bithionol, a cytotoxic organochlorine, was recently found to inhibit sAC by binding to the BBS and this connecting channel 45 , similar to ASI-8. And bithionol indeed inhibits sAC by at least partially competing with substrate ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LRE1 combines high potency and selectivity with stability, solubility and, most importantly, lack of cytotoxicity. In particular, LRE1 exhibits less non-specific toxicity than KH7, the widely used sAC specific inhibitor 2 , 27 , and bithionol, a recently characterized sAC selective inhibitor 45 . Therefore, LRE1 is an ideal candidate to explore the therapeutic possibilities of sAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…• Bithionol is a halogenated anti-infective agent that is used against trematode and cestode infestations. This drug inhibits human soluble adenylyl cyclase (Kleinboelting et al 2016).…”
Section: Resultsmentioning
confidence: 99%